2019
DOI: 10.1186/s12931-019-1186-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils from severe asthmatic patients induce epithelial to mesenchymal transition in healthy bronchial epithelial cells

Abstract: BackgroundAsthma is a heterogenous disease characterized by chronic inflammation and airway remodeling. An increase in the severity of airway remodeling is associated with a more severe form of asthma. There is increasing interest in the epithelial to mesenchymal transition process and mechanisms involved in the differentiation and repair of the airway epithelium, especially as they apply to severe asthma. Growing evidence suggests that Epithelial-Mesenchymal transition (EMT) could contribute to airway remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
1
28
0
4
Order By: Relevance
“…Neutrophils are well-documented because of their aggravating role in inflammation ( 114 ), where neutrophil-to-lymphocyte ratio is a popular prognostic marker for estimating the mortality of CKD patients ( 115 ). Neutrophils can initiate and amplify inflammatory responses by releasing pro-inflammatory cytokines ( 114 , 116 ), and serves as a rich source of TGF-β1 in inflamed tissues ( 117 , 118 ). During inflammation, TGF-β1 facilitates the accumulation of neutrophils ( 119 , 120 ), therefore inhibiting TGF-β1 effectively alleviates neutrophil infiltration and inflammation ( 121 ).…”
Section: Tgf-β1 In Adaptive Immunity Of Ckdmentioning
confidence: 99%
“…Neutrophils are well-documented because of their aggravating role in inflammation ( 114 ), where neutrophil-to-lymphocyte ratio is a popular prognostic marker for estimating the mortality of CKD patients ( 115 ). Neutrophils can initiate and amplify inflammatory responses by releasing pro-inflammatory cytokines ( 114 , 116 ), and serves as a rich source of TGF-β1 in inflamed tissues ( 117 , 118 ). During inflammation, TGF-β1 facilitates the accumulation of neutrophils ( 119 , 120 ), therefore inhibiting TGF-β1 effectively alleviates neutrophil infiltration and inflammation ( 121 ).…”
Section: Tgf-β1 In Adaptive Immunity Of Ckdmentioning
confidence: 99%
“…Ремоделирование подразумевает под собой структурные изменения, такие как: увеличение массы гладких мышц, потеря целостности эпителия, утолщение базальной мембраны, субэпителиальный фиброз, гиперплазия подслизистой, снижение целостности хряща и повышение васкуляризации дыхательных путей [6]. Степень ремоделирования дыхательных путей положительно коррелирует с тяжестью заболевания [7].…”
Section: патофизиология фодпunclassified
“…They were cultured in DMEM containing 10% fetal bovine serum (Gibco BRL) and 1% penicillin/streptomycin (Gibco BRL) at 37 • C with 5% CO 2 . They were stimulated with recombinant human TGF-β1 (Abcam, ab166886) at 10 ng/mL for 48 h to induce EMT as previously described (Itoigawa et al, 2015;Haddad et al, 2019). During some experiments, BEAS−2B was pretreated with RPYD (5 µmol/L), TGFβ1 inhibitor SB431542 (10 µM, CST, #14775, United States), or NOTCH1 inhibitor DAPT (10 µM, CST, #15020, United States) for 6 h before TGF-β1 stimulation.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Studies have shown that TGFβ1 induces and promotes the occurrence of EMT (Haddad et al, 2019;Song et al, 2018). Therefore, TGFβ1 was used as an agonist to induce the occurrence of EMT in BEAS-2B cells.…”
Section: Rpyd Reduces the Emt By Inhibiting The Phosphorylation Of Smmentioning
confidence: 99%